Individual Differences in Relational Learning and Analogical Reasoning: A Computational Model of Longitudinal Change - Doumas, Leonidas A. A.; Morrison, Robert G.; Richland, Lindsey E. (Frontiers in Psychology, 2018)
Children’s cognitive control and knowledge at school entry predict growth rates in analogical reasoning skill over time; however, the mechanisms by which these factors interact and impact learning are unclear. We propose that inhibitory control is critical for developing both the relational representations necessary to reason and the ability to use these representations in complex problem solving. We evaluate this hypothesis using computational simulations in a model of analogical thinking, DORA/LISA (Discovery Of Relations by Analogy; Doumas, Hummel, & Sandhofer, 2008). Longitudinal data from children who solved geometric analogy problems repeatedly over six months show three distinct learning trajectories though all gained somewhat: analogical reasoners throughout, non-analogical reasoners throughout, and transitional - those who start non-analogical and grew to be analogical. Varying the base level of top-down lateral inhibition in DORA affected the model’s ability to learn relational representations, which, in conjunction with inhibition levels used in LISA during reasoning, simulated accuracy rates and error types seen in the three different learning trajectories. These simulations suggest inhibitory control may not only impact reasoning ability but may also shape the ability to acquire relational knowledge given reasoning opportunities.